Dziecięce wyobrażenia paidii - Guzy, Anna (Paidia i Literatura, 2019)
This chapter consists of two parts: theoretical background and case studies. It aims at presenting children’s fantasies or mental images (be it verbal or iconic) of paidia as a word. The first part is dedicated to the investigations into children’s imagination, stages of its development, and factors that affect it. The other part analyses the works of 51 pupils who were supposed to draw “a paidia” and reads the ways they both concretised it on the pictures and described them.